2019
DOI: 10.4103/ijnm.ijnm_94_18
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of maximum standardized uptake values in 18F-Fluorodeoxyglucose positron emission tomography-computed tomography scan with immunohistochemistry and other prognostic factors in breast cancer

Abstract: Objectives:The objective of this study was to correlate maximum standardized uptake value (SUVmax) with different immunohistochemical subtypes of breast cancer and other prognostic factors in breast cancer.Subjects and Methods:This was a retrospective study including 219 consecutive patients undergoing whole-body fluorodeoxyglucose positron emission tomography/computed tomography scan for the staging of breast cancer. Out of 219 patients, two were male and 217 were female; age ranged from 26 to 85 years with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
(23 reference statements)
7
5
1
Order By: Relevance
“…In the present study, the SUVmax are in the following order: luminal A < luminal B < Her2 enriched < TNBC. The SUVmax of the primary lesion increases with an increase in the size of the tumor (p = 0.01), similar to the findings by Lee et al, 12 Sanli et al, 15 Abubakar et al 16 Likewise, the stratification of T4 tumors by size (to <5 cm and >5 cm) has shown higher SUVmax in larger tumors but was not significant (p = 0.94).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, the SUVmax are in the following order: luminal A < luminal B < Her2 enriched < TNBC. The SUVmax of the primary lesion increases with an increase in the size of the tumor (p = 0.01), similar to the findings by Lee et al, 12 Sanli et al, 15 Abubakar et al 16 Likewise, the stratification of T4 tumors by size (to <5 cm and >5 cm) has shown higher SUVmax in larger tumors but was not significant (p = 0.94).…”
Section: Discussionsupporting
confidence: 85%
“…Proliferation indices such as ki‐67 and MIB1 are proven biomarkers in breast cancer, but they were not analyzed due to the paucity of available data. The SUVmax of the primary lesion increases with an increase in the size of the tumor ( p = 0.01), similar to the findings by Lee et al., 12 Sanli et al., 15 Abubakar et al 16 . Likewise, the stratification of T4 tumors by size (to <5 cm and >5 cm) has shown higher SUVmax in larger tumors but was not significant ( p = 0.94).…”
Section: Discussionsupporting
confidence: 85%
“…For example, although PET scans are highly effective in the detection of extra-axillary nodal and distant metastases in more locally advanced breast cancers, they have not demonstrated significant benefit for patients with early-stage breast cancer. [2][3][4] Furthermore, although some studies suggest a potential diagnostic benefit of PET-CT for clinical stage IIB patients, these imaging modalities do not show significant benefit in the detection of distant metastases in early-stage breast cancers with low likelihood of metastatic spread, such as ductal carcinoma in situ and lesions clinically staged as I and IIA. [5][6][7][8] Thus, although CT and PET-CT can be instrumental in the identification of distant metastases in clinically advanced breast cancer, their use in early-stage breast cancers is low in yield relative to false-positive rates.…”
Section: Introductionmentioning
confidence: 99%
“…The preferred method to stage breast cancer patients was also changed from chest X-ray and abdominal ultrasound to a computerized axial tomography (CAT) scan of the thorax and abdomen [5]. The reason for this proposal is the higher sensitivity of the latter, although only data of a direct comparison between conventional staging and PET/CT exist [10,11].…”
Section: Introductionmentioning
confidence: 99%